Twilight : the complete illustrated movie companion - Vaz, Mark Cotta (New York : Little, Brown and Company, 2008)
Designed as a celebration of the film, this lavishly illustrated paperback edition is an exclusive behind-the-scenes guide featuring full-color photos of the cast, locations, and sets, as well as storyboards, interviews, details of the special effects, and much more.
Includes bibliographical references .